SISTEM INFORMASI PENGOLAHAN DATA ASPROV PSSI PROVINSI JAMBI: Asprov PSSI, Data Processing, Football, Information System, Information Technology, Waterfall Method - Adriana, Windy; Astuti, Reny Wahyuning; Ramadhan, Fajar; Windy Adriana (FORTECH (Journal of Information Technology), 2025)
The rapid development of information technology and computers has influenced various aspects of life, including sports. In the context of football, data management is a crucial element in enhancing athlete performance and operational efficiency. The Provincial Association (Asprov) of PSSIJambi Province is currently facing challenges in managing data manually, often leading to errors and information loss. To address this issue, this research aims to design and develop a web-based "Data Management Information System for Asprov PSSI Jambi Province." The system is designed to efficiently process data related to athletes, referees, clubs, Football Schools (SSB), and matches using PHP, CSS, HTML, and MySQL database technology. The research methodology used is a qualitative approach with the waterfall model, encompassing stages of analysis, design, testing, implementation, and system maintenance. This application is expected to improve the speed and accuracy of data processing and reduce errors in data management.